2018
DOI: 10.1039/c8fo01143e
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic acid disrupts the intestinal mucosal barrier and promotes intestinal tumorigenesis

Abstract: Deoxycholic acid (DCA) induced intestinal low grade inflammation and disrupted the mucosal physical and functional barriers, aggravating intestinal tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 52 publications
2
67
0
Order By: Relevance
“…Clostridium species catabolize cholic acid to deoxycholic acid for their growth [152]. It is reported that, in mice, deoxycholic acid increases intestinal permeability through the reduction of goblet cell number, suppression of mucin production, induction of low-grade inflammation, and suppression of tight junction protein (ZO-1) expression [153]. In terms of dietary factors that reduce Escherichia , there are many reports of sulfated polysaccharides (Table 4).…”
Section: Association Of Dietary Factor-induced Reduction Of Blood mentioning
confidence: 99%
“…Clostridium species catabolize cholic acid to deoxycholic acid for their growth [152]. It is reported that, in mice, deoxycholic acid increases intestinal permeability through the reduction of goblet cell number, suppression of mucin production, induction of low-grade inflammation, and suppression of tight junction protein (ZO-1) expression [153]. In terms of dietary factors that reduce Escherichia , there are many reports of sulfated polysaccharides (Table 4).…”
Section: Association Of Dietary Factor-induced Reduction Of Blood mentioning
confidence: 99%
“…Interestingly, high-fat diet has also been associated with NLRP3 activation and increased tumor susceptibility [162,169]. High-fat diet leads to an increase in deoxycholic acid levels in the intestine, which, in turn, disrupts the cell monolayer integrity by decreasing the expression of the tight junction protein ZO-1 [170]. This disruption in the mucosal barrier leads to an increased tissue inflammation, mediated by NLRP3, and further polarization of M2 macrophages [162].…”
Section: Impact Of Nlrs On Cancermentioning
confidence: 99%
“…Oxidative stress level of the intestine was closely related to the integrity of histological morphology 22,37,38 . Ileal mucosal permeability was shown to be protected by Se‐enriched Agaricus bisporus mushroom by upregulating the mRNA expression of GPx in rats 7 .…”
Section: Resultsmentioning
confidence: 98%